PRODUKSI DAN NILAI NUTRISI HIJAUAN JAGUNG MANIS (ZEA MAYSSACCHARATA) DENGAN PEMUPUKAN FOSFAT DAN INOKULASI MIKORIZA PADA KONDISI TANAH BERBEDA - Dwi Retno Lukiwati; Robert Djonggi Maruli Simanungkalit (JURNAL LITBANG PROVINSI JAWA TENGAH, 2003)
Rock phosphate (RP) fertilizer belongs to slow available source of phosphorus compared to superphosphate (SP), and mycorrhiza inoculation maybe a promising technique to overcome the problem. The symbiosis between mycorrhiza and Zea mays saccharaiaSturt in unsterilized soil has been less studied compared to sterilized soil. A greenhouse experiment was con• ducted on acid latosolic soiland low phosphorus availability. The experimental design was a factorial 2x2x3 in 3 replicates. The treatments were soil sterilization (unsterilized, sterilized), mycorrhiza inoculation (uninoculated, inoculated) and P fertilization (RP-10, RP-20, SP-36). All pots received fertilization of 200 kg N/ha (6 g urea/pot), 150 kg K20/ha (3.50 g KCl/pot) and 150 kg P20/ha of three kinds of P fertilizer source were RP-10 (21 g/pot), RP- 20 (10.50 g/pot) and SP-36 (6 g/pot). The latosolic soil was sterilized by autoclaf at 121°c for 15 minutes. Each pot contain 8 kg dry soil and inoculated by 40 g soil inoculum of Glomus manihotis according to the assigned treatment at the time of planting. Each pot contain 2 plants of Zea mays saccharata Sturt. Zea mays was cut at ground level at 6 wekks after planting and analyzed for dry matter (DM), N and P content. Dry matter production, N and P uptake with SP fertilizer were significantly higher compared to RP (RP-IO, RP-20) on both srreilized soil and unsterilized soil. Dry matter production, N and P uptake with SP fertilizer on sterilized soil were significantly higher compared to unsterilized soil, while RP fertilizers (RP-10, RP-20) were not significantly different. The DM production, N and P uptake of Zea mays were not significantly affected by the interaction.between the treatments of mycorrhiza inoculation, P fertilization and soil sterilization.